A practical, quantitative, fracture healing endpoint assessment criterion for tibial fractures treated with external fixation. (May 2019) - Ogrodnik, Peter J; Thomas, Peter BM
There is a need for a quick, simple, repeatable, but quantifiable assessment tool to determine the fracture healing endpoint of tibial fractures that does not rely on the use of X-rays or on un-measured manipulation. This article presents an argument to support a 'maximum of 1° bending' criterion. The criterion was established from an examination of patient fracture stiffness profiles and following observations of stiffness measurements made in clinics. A proprietary mono-lateral external fixator was used to test the criterion. Sixty subjects had their fracture healing endpoint assessed using this criterion compared with the 15 N m/deg in two planes criterion, and it was deemed to be successful. The method of assessment for both mono-lateral and frame fixation (Ilizarov) is demonstrated.